Global Productivity : Trends, Drivers, and Policies - Dieppe, Alistair (Washington, DC: World Bank, 2020)
The COVID-19 pandemic struck the global economy after a decade that featured a broad-based slowdown in productivity growth. Global Productivity: Trends, Drivers, and Policies presents the first comprehensive analysis of the evolution and drivers of productivity growth, examines the effects of COVID-19 on productivity, and discusses a wide-range of policies needed to rekindle productivity growth. The book also provides a far-reaching dataset of multiple measures of productivity for up to 164 advanced economies and emerging market and developing economies and introduces a new sectoral database of productivity.